1991
DOI: 10.1182/blood.v78.3.711.711
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of CD45 isoforms defines CALLA+ monoclonal B- lineage cells in peripheral blood from myeloma patients as late stage B cells

Abstract: The peripheral blood lymphocytes from 42 patients with multiple myeloma (MM) and 13 patients with monoclonal gammopathy of undetermined significance (MGUS) were studied by three-color immunofluorescence (IF) using antibodies directed to a broad range of B-cell markers (CD19, CD20, CD21, CD24), CALLA (CD10), PCA-1 (a plasma cell marker), and to the high and low molecular weight isoforms of the leukocyte common antigen, CD45RA (p205/220) and CD45RO (p 180). CD45RA is expressed on pre-B and B cells, and a transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(38 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…The present study demonstrates that the percentage and the absolute number of PB CD19 þ B cells were clearly decreased in MM patients when compared with healthy subjects. Although other authors have found high [4] or normal [5,6] numbers of PB B cells in MM, chemotherapy cannot be the basis for this disagreement, since all of our MM patients were studied at diagnosis and had not yet received treatment. The extreme heterogeneity of this disease [25,26] may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The present study demonstrates that the percentage and the absolute number of PB CD19 þ B cells were clearly decreased in MM patients when compared with healthy subjects. Although other authors have found high [4] or normal [5,6] numbers of PB B cells in MM, chemotherapy cannot be the basis for this disagreement, since all of our MM patients were studied at diagnosis and had not yet received treatment. The extreme heterogeneity of this disease [25,26] may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 76%
“…There is, however, general agreement on the assumption that monoclonal circulating B lymphocytes in MM are limited to a very reduced B cell subset [2,13]. Nevertheless, massive alterations have been described in the number as well as in the surface molecule expression of PB B cells from MM patients [4], including adhesion receptors [14]. Adhesion molecules are cell surface proteins which have been shown to be important in mediating adhesion of a variety of cell types to other cells and to components of the extracellular matrix [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have detected B cells with expression of antigens including CD10 (Jensen et al, 1991), CD34 (Belch et al, 1996), CD45RO (Jensen et al, 1991) and CD56 (Bergsagel et al, 1995) in the peripheral blood of patients with myeloma. We were unable to detect such cells, and found that the phenotypic profile of B lymphocytes from myeloma patients was identical to those from normal donors, with variation only in the numbers of particular subsets.…”
Section: Discussionmentioning
confidence: 99%
“…The second supposition cannot be ruled out but gives no explanation for the existence of a proliferating B lymphocyte population, which has been observed carrying the same idiotype and the same gene rearrangement as the plasmocytic cells and which have been recognized as malignant progenitor cells by various investigators (5, (,,8,22,31,40-42,4(,,48,53). There are studies showing that, in MM, a population of pre-B cells is the target for an oncogenic event, which does not block differentiation to plasmocytic cells ( 12,17,22,23,27,32,37,43,45,47). The third possiblity is equivocal but may be correct.…”
Section: Discussionmentioning
confidence: 99%